Progression of nuclear sclerosis based on changes in refractive values after lens-sparing vitrectomy in proliferative diabetic retinopathy - Ikeda T (Dove Medical Press, 2014)
Tsunehiko Ikeda,1 Masahiro Minami,1 Kimitoshi Nakamura,2 Teruyo Kida,1 Masanori Fukumoto,1 Takaki Sato,1 Eisuke Ishizaki11Department of Ophthalmology, Osaka Medical College, Osaka, Japan; 2Nakamura Eye Clinic, Nagano, JapanBackground: Nuclear sclerosis (NS) based on the Emery–Little classification and refractive values after lens-sparing vitrectomy was compared between proliferative diabetic retinopathy (DR) patients and nondiabetic patients.Methods: Progression of NS based on the Emery–Little classification and changes in refractive values were compared between 13 proliferative DR patients (14 eyes, DR group) and 14 nondiabetic patients (14 eyes, non-DR group) who underwent lens-sparing vitrectomy. All patients revealed grade I NS based on the Emery–Little classification. Mean patient age and refractive value just after surgery were 56.07 years and −0.33 diopters (D) in the DR group, and 57.06 years and −0.96 D in the non-DR group.Results: The Emery–Little classification in the DR group at 6 and 24 months postoperative were grade I (13 eyes)/grade II (one eye) and grade I (eleven eyes)/grade II (three eyes), respectively. Mean refractive values in the DR group at 6, 12, and 24 months postoperative were +0.28 D, +0.27 D, and +0.37 D, respectively. The Emery–Little classification in the non-DR group at 6 and 24 months (or preoperative for patients undergoing cataract surgery) were grade I (five eyes)/grade II (eight eyes) and grade I (zero eyes)/grade II (eight eyes)/grade III (five eyes), respectively. The mean refractive value in the non-DR group at 6 months postoperative was −3.20 D. All eyes exhibited myopic changes and progression of NS.Conclusion: The findings of this study show that the progression of NS postvitrectomy is mild, even for DR patients 50 years of age or older, thus suggesting the need to reconsider the indications for simultaneous cataract surgery with vitrectomy.Keywords: Emery–Little classification